Does Financial Literation Moderate The Effect of Funding on The Sustainability of Micro Enterprises - Dody Hapsoro; Adrian Septia Iswara (The Indonesian Journal of Accounting Research, 2019)
Financing is one of the main supporting factors in the sustainability of micro businesses. Micro businesses are expected to be able to manage company finances professionally for the benefit and sustainability of their business. The purpose of this study is to examine financial literacy skills in moderating the effect of financing on the sustainability of micro businesses. The variables tested were financing, financial literacy and business sustainability.The population in this study is a micro-business that runs its business activities in Blora Regency, Central Java. The number of samples used in this study were 120 micro businesses, which were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is simple regression and multiple regression using SPSS version 25.0. The results showed that financing has a positive effect on the sustainability of micro businesses and financial literacy strengthens the effect of financing on the sustainability of micro businesses.The implication of this study is that micro entrepreneurs are expected to be able to improve financial literacy skills, especially in terms of fund management because funds obtained from financing activities are vulnerable to the possibility of fraud and mismanagement.